Android Based Li-Ion Battery BMS Protection - Erisika Dian Samudra; Denny Irawan (LPPM Universitas Dian Nuswantoro, 2026)
Along with the growing demand for energy in portable devices and modern energy storage systems, lithium-ion (Li-Ion) batteries have become one of the primary solutions due to their high energy density, efficiency, and long cycle life. However, this type of battery is highly sensitive to conditions such as overcharging, over-discharging, high temperature, and voltage imbalance between cells, which can significantly reduce performance and lifespan. To address these issues, an intelligent monitoring and protection system known as the Battery Management System (BMS) is required. In this study, an integrated IoT-based monitoring system using the Blynk platform was developed to enhance the BMS monitoring functionality for Li-Ion 18650 battery packs in real-time and remotely. The proposed system utilizes an ESP32 microcontroller as the main controller connected to current, voltage, and temperature sensors. The measurement data are transmitted via Wi-Fi to the Blynk Cloud server and displayed through the Blynk IoT mobile dashboard. This research adopts an experimental and implementation approach. The developed system successfully monitored voltage, current, temperature, and SoC in real time through the Blynk IoT platform while executing automatic protection under abnormal conditions. Keywords - Battery Management System, Li-Ion 18650, Internet of Things, ESP32, Blynk IoT